1963
DOI: 10.1139/y63-162
|View full text |Cite
|
Sign up to set email alerts
|

Transamination in Muscular Dystrophy and the Effect of Exogenous Glutamate: A Study on Vitamin E Deficient Rabbits, and Mice With Hereditary Dystrophy

Abstract: A study of transaminase enzymes in various tissues of different species was carried out. Rabbits were fed with a vitamin E deficient diet. Controls receiving vitamin E were maintained on the same diet. Animals were killed at intervals and the glutamic-aspartic transaminase (GOT) and the glutamic-alanine transaminase (GPT) levels were determined in the muscle, blood, and liver.Mice with hereditary muscular dystrophy and normal litter mates which served as controls were killed at different stages of the disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1964
1964
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…The loss of A1AT activity was more than that of AAT suggesting that the former was greatly affected on denervation. The skeletal muscle of vitamin E deficient rabbits at the severe stage of the dystrophic process had also been observed to exhibit such greater loss of A1AT than AAT [22]. The aminotransferase activities in different tissues and serum of normal and denervated frogs were similar (table II).…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…The loss of A1AT activity was more than that of AAT suggesting that the former was greatly affected on denervation. The skeletal muscle of vitamin E deficient rabbits at the severe stage of the dystrophic process had also been observed to exhibit such greater loss of A1AT than AAT [22]. The aminotransferase activities in different tissues and serum of normal and denervated frogs were similar (table II).…”
Section: Resultsmentioning
confidence: 89%
“…Previous investigations on the amino transferase activities of the vitamin E deficient rabbits and mice with hereditary muscular dystrophy indicated that both the AAT and A1AT activities of skeletal muscle were slightly elevated at the pre liminary stage and considerably decreased at the acute stage of the dystrophic process [22]. The observed decrement in the level of amino transferase activities in frog muscle denervated for 1 month in the present study may represent the acute stage of the dystrophic pro cess as observed in rabbits and mice [22]. But the serum aminotrans ferase levels were found to be significantly elevated in the dystrophic animals with a concomitant decrease in the skeletal muscle.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Intracellular degradation of myofibrillar proteins also release glutamic acid with large amounts contributing to the muscle glutamic acid pool [ 26 ]. The role of glutamic acid in muscular dystrophy was studied in the early 1960s in rabbit models (due to vitamin E deprivation) [ 27 ]. In these studies, body weight loss and the onset of terminal disease was accelerated when animals were given exogenous glutamic acid [ 27 ].…”
Section: Discussionmentioning
confidence: 99%